Capacity Building of Lalowosula Village Community in Drafting Responsive and Participatory Village Regulation: Pengembangan Kapasistas Masyarakat Desa Lalowosula Dalam Penyusunan Produk Hukum yang Responsif dan Partisipatif - Saldi, Winatri; Wahyudi Umar; Rustan, Ahmad; Hindi Asis, Patta (Universitas Muhammadiyah Malang, 2025)
This community service program aims to enhance the legal drafting capacity of the community and village government of Lalowosula Village, East Kolaka Regency, focusing on the development of responsive and participatory local regulations. The low level of legal literacy, limited participation, and lack of access to regulatory information constitute the main challenges in village governance. The method applied in this program consists of five stages: preparation, socialization, legal counseling, technical training, and mentoring. The activity involved village officials, BPD members, and community legal awareness groups. The results show a significant increase in participants’ understanding of legal drafting techniques and community participation in formulating public policies. The program also successfully developed an interactive website that provides legal drafting guidelines and online administrative services for villagers living outside the region. The community expressed positive responses toward the training and indicated readiness to participate in future policymaking processes. This service program has contributed to strengthening legal awareness, improving policy quality, and promoting participatory village governance practices. This program offers a replicable model for integrating digital tools into village-level legal drafting and participatory governance in Indonesia. Abstrak Program pengabdian ini bertujuan meningkatkan kapasitas masyarakat dan pemerintah Desa Lalowosula, Kabupaten Kolaka Timur, dalam penyusunan produk hukum desa yang responsif dan partisipatif. Rendahnya literasi hukum, minimnya partisipasi masyarakat, serta terbatasnya akses informasi regulasi merupakan tantangan utama dalam tata kelola desa. Metode pengabdian dilakukan melalui lima tahapan: persiapan, sosialisasi, penyuluhan hukum, pelatihan teknis, dan pendampingan. Kegiatan melibatkan aparat desa, anggota BPD, serta kelompok keluarga sadar hukum. Hasil kegiatan menunjukkan peningkatan signifikan terhadap pemahaman peserta mengenai teknik penyusunan peraturan desa serta meningkatnya partisipasi warga dalam merumuskan kebijakan publik. Program ini juga berhasil mengembangkan website interaktif yang menyediakan panduan penyusunan peraturan desa serta layanan administrasi online bagi warga yang tinggal di luar daerah. Masyarakat memberikan respon positif dan menunjukkan kesiapan untuk terlibat dalam proses legislasi desa. Program ini berkontribusi pada penguatan kesadaran hukum, peningkatan kualitas kebijakan desa, dan pengembangan praktik tata kelola desa yang partisipatif. Program ini menawarkan model yang dapat direplikasi untuk mengintegrasikan perangkat digital ke dalam penyusunan hukum tingkat desa dan tata kelola partisipatif di Indonesia.